1998
DOI: 10.1046/j.1365-313x.1998.00062.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane depolarization‐activated calcium channels, stimulated by microtubule‐depolymerizing drugs in wild‐type Arabidopsis thaliana protoplasts, display constitutively large activities and a longer half‐life in ton 2 mutant cells affected in the organization of cortical microtubules

Abstract: SummaryDepolarization-activated plasma membrane calcium channels have been suggested to play prominent roles in signal perception and transduction processes during growth and development of higher plants. The existence of such channels has recently been established in higher plant cells. However, patch-clamp experiments have shown that their activity is very low and decreases very rapidly after the establishment of the whole-cell configuration, due most probably to protein-protein interactions involving microt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
81
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(83 citation statements)
references
References 38 publications
1
81
1
Order By: Relevance
“…As both of these channels are TEA 1 sensitive, inhibition of K 1 efflux by TEA 1 in our experiments (Fig. 7) (Thion et al, 1998;Miedema et al, 2001). These play a prominent role in signal perception and transduction in plants (Thion et al, 1998).…”
supporting
confidence: 56%
See 1 more Smart Citation
“…As both of these channels are TEA 1 sensitive, inhibition of K 1 efflux by TEA 1 in our experiments (Fig. 7) (Thion et al, 1998;Miedema et al, 2001). These play a prominent role in signal perception and transduction in plants (Thion et al, 1998).…”
supporting
confidence: 56%
“…7) (Thion et al, 1998;Miedema et al, 2001). These play a prominent role in signal perception and transduction in plants (Thion et al, 1998). Regardless of the type of Ca 21 -permeable channel, increased Ca 21 uptake will provide a positive feedback to further depolarize the membrane potential, amplifying the effect of phenolics on K 1 transport (as depicted in a tentative model in Fig.…”
mentioning
confidence: 99%
“…Although the properties of DACCs and HACCs are well studied electrophysiologically (Grabov and Blatt, 1998;Thion et al, 1998;Thuleau et al, 1998;Hamilton et al, 2000;Pei et al, 2000;Klusener et al, 2002), the molecular identity of these channels is still unknown . It is assumed that DACCs contribute to the short transient influx of Ca 2+ in response to various stimuli, including chilling and microbe interaction (Thion et al, 1998). HACCs contribute to a sustained Ca 2+ influx in response to ABA (Hamilton et al, 2000;Pei et al, 2000), blue light (Harada and Shimazaki, 2009), and Ca 2+ nutrition (Miedema et al, 2001(Miedema et al, , 2008.…”
Section: Voltage-dependent Channels At the Plasma Membranementioning
confidence: 99%
“…Several Arabidopsis mutants, such as fass (Torres-Ruiz and Jürgens, 1994;McClinton and Sung, 1997), ton1 and ton2 (Traas et al, 1995;Thion et al, 1998), cho (Mayer et al, 1999), hal (Mayer et al, 1999), pfi (Mayer et al, 1999), por (Mayer et al, 1999), fra2/bot1 (Bichet et al, 2001;Burk et al, 2001), and mor1 (Whittington et al, 2001), have been shown to alter cortical MT patterns and affect cellular morphology. The genes for two of these mutants have been cloned and characterized.…”
Section: Introductionmentioning
confidence: 99%